Pengaruh Komunikasi Pelayanan Berbasis Aplikasi Terhadap Kepuasan Nasabah PT.Pegadaian Cabang Tarandam Kota Padang - Rahmad Fikri Januarta; Indria Flowerina (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
The background of this study is based on the development of digitalization in financial services, which has encouraged PT. Pegadaian Tarandam Branch to adopt application-based communication to enhance service quality and customer satisfaction. In the digital era, effective communication through applications plays a crucial role in building customer loyalty. This study aims to analyze the influence of application-based service communication on customer satisfaction at PT. Pegadaian Tarandam Branch, Padang City. The research employs a descriptive quantitative method with a purposive sampling technique, involving 50 respondents who are active users of the Pegadaian Digital application. Data were collected using a Likert-scale-based questionnaire and analyzed through simple linear regression tests, validity tests, reliability tests, and classical assumption tests using SPSS version 30. The results show that application-based digital communication has a significant influence on customer satisfaction. The key dimensions in improving service quality include reliability, responsiveness, empathy, and assurance. Overall, application-based digital communication contributes 61% to customer satisfaction, while the remaining 39% is influenced by other variables. The findings suggest that optimizing application features and service quality can enhance customer loyalty and trust in Pegadaian’s services.